PSIKOLOGI TOKOH KORBAN KOMUNIS DALAM CERPEN SURAT UNDANGAN, KERBAU BERTANDUK EMAS KARYA PUTU OKA SUKANTA, DAN TANAH AIR KARYA MARTIN ALEIDA - Tiara, Mafi Sri Wahyu; Haryanti, Novi Diah (MEDAN MAKNA: Jurnal Ilmu Kebahasaan dan Kesastraan, 2023)
G30S is one of the great tragedies recorded in Indonesian history because it led an unreasonable number of casualties. It started with the emergence of a rebellion movement carried out by the communist party, triggering resistance that demanded the lives of many innocent victims. Several resistance and unfair treatment in several areas then occurred as an effort to wipe out descendants and people suspected of being communists in Indonesia. Apart from cruel detention and torture which resulted in physical injuries and bloodshed, this dark incident little by little eroded the mental condition of the victims and did not hesitate to kill them slowly. This research examines the psychology of communist victim characters in the short stories Surat Undangan, Kerbau Bertanduk Emas by Putu Oka Sukanta, and Tanah Air by Martin Aleida. The stories studied are equally themed about the suffering of the 1965 tragedy that was felt by the victims of the communists. This study uses a literary psychology approach according to Sigmund Freud's theory. The data in this study were found through comparative literature and qualitative descriptive methods using reading and note-taking techniques. The results of the research show that there are three psychological elements found in the victim character, namely Id, Ego, and Super ego. As a result of the victim's trauma, the form of ID shown in some of the data in the text occurs consciously, semi-consciously, or in a state that is not truly conscious. The form of the ego is photographed through the actions of victims that occur in reality or general reality. While the Super ego is the action of the victim character in the text which is motivated by the dominance of moral attitudes and politeness.